Advantages of Computer Simulation in Enhancing Students' Learning About Landform Evolution: A Case Study Using the Grand Canyon. Issue 1 (15th February 2016) - Luo, Wei; Pelletier, Jon; Duffin, Kirk; Ormand, Carol; Hung, Wei-chen; Shernoff, David J.; Zhai, Xiaoming; Iverson, Ellen; Whalley, Kyle; Gallaher, Courtney; Furness, Walter
ABSTRACT: The long geological time needed for landform development and evolution poses a challenge for understanding and appreciating the processes involved. The Web-based Interactive Landform Simulation Model—Grand Canyon (WILSIM-GC, http://serc.carleton.edu/landform/ ) is an educational tool designed to help students better understand such processes, using the Grand Canyon as an example. Although the project is still ongoing, here, we present the initial results of using the WILSIM-GC in an introductory physical geography laboratory course. We used a quasiexperimental design to assess the efficacy of WILSIM-GC as a tool for teaching landform development and evolution. Students were assigned to a control group or a treatment group, alphabetically by last name. Pretests and posttests were administered to measure students' understanding of the concepts and processes related to Grand Canyon formation and evolution. Results show that, although both the interactive simulation and a more-traditional, paper-based exercise were effective in helping students learn landform evolution processes, there were several advantages and affordances to the simulation approach. The improvement effect from pretest to posttest scores was large for the treatment group, but small to moderate for the control group. In addition, for those questions requiring higher-level thinking, the percentage of students answering correctly was higher in the treatment group than it was in the control group. Furthermore, responses to the attitudinal survey indicate that students generally favor the interactive simulation approach. We can leverage these advantages to enhance students' learning by integrating interactive simulation exercises into curricular materials, including materials for online or hybrid courses and flipped classrooms.